Penerapan Metode Bernyanyi Dalam Meningkatkan Minat Belajar Siswa pada Mata Pelajaran IPS - Damayanti, Wanisa; Fitri, Nur Laily; Wandini, Rora Rizky (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
IPS education and learning is one very important aspect that needs to be taught in schools. But in fact, one of the problems why social studies education is so difficult to integrate, one of which is the role of the teacher himself. In presenting the material, the teacher gave more lengthy lectures so that social studies learning was considered less interesting by students. As a result, this learning has a relatively small effect on increasing student understanding during the learning process and influencing student learning outcomes. One way that can be done by a teacher is by applying the singing method in the learning process. With this singing method, students can strengthen their memory of the material learned with songs, because something interesting and fun is easier to remember. This study uses quantitative research with library research data collection techniques (Library Research). The results of this study indicate that the singing method has an effect on student learning outcomes. Keywords: Singing Method, IPS, Learning Outcomes.